2018
DOI: 10.1177/0734242x18812651
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of the organic fraction of municipal solid waste

Abstract: The appropriate selection of treatment or final disposal for municipal solid waste generated by a population depends on multiple characteristics; decision-making becomes a challenge for those responsible for its integral management. Therefore, the objective of this research was to evaluate multi-scenarios of valorisation of the organic fraction of municipal solid waste. The methodology used included a sample of 421 houses to determine the generation and composition of the aforementioned municipal solid waste; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Begum et al (2018) facilitated high-rate co-digestion of mixed organic wastes and reported positive ramification on the biogas yield. A techno-economic evaluation of pilot AD in continuous mode would be interesting in order to assess other factors than the mixing ratio for full-scale applications (Achinas and Euverink, 2019; Baccioli et al, 2019; Benato and Macor, 2019; Carlini et al, 2017; De Medina-Salas et al, 2019). In addition, we recommend an in-depth analysis of microbiome heterogeneity to assess the activity discrepancies between microbial communities.…”
Section: Resultsmentioning
confidence: 99%
“…Begum et al (2018) facilitated high-rate co-digestion of mixed organic wastes and reported positive ramification on the biogas yield. A techno-economic evaluation of pilot AD in continuous mode would be interesting in order to assess other factors than the mixing ratio for full-scale applications (Achinas and Euverink, 2019; Baccioli et al, 2019; Benato and Macor, 2019; Carlini et al, 2017; De Medina-Salas et al, 2019). In addition, we recommend an in-depth analysis of microbiome heterogeneity to assess the activity discrepancies between microbial communities.…”
Section: Resultsmentioning
confidence: 99%
“…A tiny portion of bio-waste is burned without recovering the abundance of valuable nutrients, and the remainder is landfilled [ 24 ]. The amount of municipal solid trash generated worldwide is estimated to be 1.3 billion Mg/year, and it is anticipated to grow in the coming years [ 25 ]. A significant portion of municipal waste, which includes food waste and green & garden waste (leaves, grass), is organic waste.…”
Section: Complexity Of the Soil Systemmentioning
confidence: 99%
“…Organic solid waste heat treatment technology mainly includes incineration technology and pyrolysis technology. Incineration is an organic solid waste heat treatment technology that burns organic solid waste directly as fuel in the boiler or is mixed with coal/biomass and then sent to the boiler for combustion, so that the combustible components in the organic solid waste undergo rapid oxidation reaction and release energy [10][11]. Although incineration technology can quickly reduce and recycle domestic waste, the inorganic components in organic solid waste are converted into incineration bottom slag and fly ash after incineration, forming environmentally hazardous waste.…”
Section: Thermal Treatment Technology Of Organic Solid Wastementioning
confidence: 99%